PROSPEK USAHATANI TEMBAKAUVO RAJANG MAESAN DI KABUPATEN JEMBER(STUDI KASUS DI KECAMATAN JELBUK) - Edi Turjono; Kabul Santoso; Imam Syafi'i (RELASI : JURNAL EKONOMI, 2015)
Edi Turjono, 041520201005, Departement of Agribusiness, Postgraduate Program, University of Jember, research title: "The Prospects of Besuki Tobacco VO Rajang Farming in Jember Recident(A Case Study in Jelbuk District)", under supervision guidance ofProf. Dr. KabulSantoso, MS, as supervisor and Ir. Imam Syafi’I, M.S., as co-supervisor. The prospect tobacco rajang Maesan farming in Jember Resident “Case study in Jelbuk District chopped tobacco farming of Maesan has an important position. So that its development should be considered by increasing the acreage and kuality; in addition hybrid corn farming is a food that has an important position after rice, and corn is needed as the ingredient for animal food indutry.This research was intended to compare the level of efficientcy of rajang tobacco farming of Maesan with that of hybrid corn farming, to analysis the variables that affected farm income of Maesan Rajang Tobacco and to indentify the prospects of Maesan rajang Tobacco farming.The analysis used in this research were: 1) R/C ratio analysis, 2) Multiple regression analysis, and SWOT (Strength, Weakness, Opprtunities and Threat) analysis.The result of analysis that the R/C ratio of rajang tobacco farming of Maesan was above the hybrid corn average R/C, while the examination of the differences between R/C ratio  commodity of rajang tobacco of Maesan and R/C of corn performed by t-test according to the independent table test. Showed that the different was with the probability. So that the probability was lower than thus, the R/C ratio hybrid corn commodities and R/C ratio of rajang tobacco Maesan  was significanly different, which means that rajang tobacco farming of Maesan was more cost-efficient than hybrid corn farming.Mean while, the variables that significantly affected Maesan rajang tobacco farming were the production of dried tobacco (X1) the selling price (X2) and Production Cost (X3). Where as the prospect of the development of the development of Maesan rajang tobacco farming was profitable for the development by considering internal and external factors in development of Maesan rajang tobacco farming in Jember Regency.